Kolaborasi Lintas Institusi untuk Penguatan Deteksi Dini Stunting berbasis Kearifan Lokal di Desa Simpasai Kabupaten Dompu - Ayatullah; Dwi Amanda; Ananda Kurnia Putri; Astuti; Sita Agustina; Abdul Rahman Manga; Fatma Afrianti Gobel; Nurul Jannah; Wahidah; Jaenab (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
The stunting prevalence in Simpasai Village, Dompu Regency, reaches 28.5%, driven by multidimensional factors such as limited understanding of nutrition, limited access to healthcare, and low income. This Student Creativity Program (Program Kreativitas Mahasiswa/PKM) aims to address these issues through an integrated approach that combines digital technology innovation and the empowerment of local food potential. The implementation method includes two main interventions. First, the introduction and implementation of the "Si-Cegah Stunting" Application, a digital platform for monitoring the nutritional status of toddlers in real-time by the cadres of the LILI Posyandu (Integrated Health Service Post), which accelerates early detection and intervention responses. Second, the empowerment of the "Mawar" Housewives Group through product innovation in the form of fortified moringa leaf cookies, rich in iron and protein, as a specific nutrition intervention strategy based on local wisdom. The implementation results show that the application successfully digitized anthropometric records, improved data accuracy, and facilitated cross-sectoral collaboration. Meanwhile, intensive training and mentoring for the housewives successfully enhanced production capacity and opened up business opportunities, contributing to increased income and access to nutritious food. This program concludes that the convergence between utilizing technology for health surveillance and optimizing local resources for nutritional intervention creates a comprehensive and sustainable stunting management model. This synergy not only addresses the root causes of nutritional problems but also empowers the community's economy, thus aligning with efforts to accelerate stunting reduction and achieve the Sustainable Development Goals (SDGs).